Analysis of acceptance and use of the agree mart mobile groceries marketplace application using the UTAUT-3 Model in Indonesia - Salman, Irfan Nurdin (Jurnal Ilmiah Pertanian dan Peternakan, 2024)
Purpose: This study aims to analyze the factors that influence user acceptance and usage of the Agree Mart mobile groceries marketplace application by applying the Unified Theory of Acceptance and Use of Technology 3 (UTAUT-3) model in the Indonesian context. Research methodology: This research method uses a mixed method by taking a sample of the population of active users in Indonesia and using samples from several respondents, and registered users who have not made transactions Results: It is hoped that this research will provide benefits to add insight and as a digital business reference and material for consideration for meeting daily needs in Indonesia in determining the right strategy both in business and application. Conclusion: The UTAUT-3 model is a useful framework for understanding grocery app adoption in Indonesia. Personal innovativeness plays a dominant role in shaping behavioral intention, while habit and infrastructure support actual usage behavior. Limitations: This study focuses only on one marketplace application (Agree Mart) and does not explore external market or competitor effects. Contribution: This research contributes to digital business strategy literature by extending the applicability of UTAUT-3 to the Indonesian e-groceries sector and providing actionable insights for platform managers to enhance user adoption and retention.